(untitled) (Vietnam Journal of Community Medicine, 2021)
Characteristics and the effectiveness of antenatal screening for chromosomal abnormalities in high-risk pregnant women in Nghe An (2020 – 2021), Screening for fetal chromosomal abnormalities is of great significance in limiting birth defects. Objective and method: To figure out chromosomal abnormalities and the value of some prenatal screening tests at Nghe An Obstetrics and Gynecology Hospital (2020-2021). Methods: 121 pregnant women who had an indication for amniocentesis were undergone ultrasound, Double test, Triple test and amniocentesis for a karyotype analysis. Results: The mean age of the participants was 32 ± 6.69 years. 62.8% of fetuses had abnormalities on ultrasound, among them the most common ones were nuchal translucency thickness (12.6%) and aplasia of the nasal bone (5.5%). The rate of chromosomal abnormality was 15.7%, of which the most common was Edwards syndrome (36.8%) followed by Down syndrome (31.6%).There was no association between fetal chromosomal abnormalities and maternal age of the pregnancy, history of pregnancy with malformations, miscarriage or family history of genetic disease. Conclusion: Ultrasound and blood screening tests have high sensitivity, high negative predictive value but low sensitivity and low positive predictive value in predicting abnormalities of fetal chromosomes.